PENGARUH PERTUMBUHAN EKONOMI, DESENTRALISASI FISKAL DAN PENDAPATAN PERKAPITA TERHADAP KEMISKINAN DI PROVINSI RIAU - Rajagukguk Binsar; Tampubolon Dahlan; Aquldo Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Poverty rates in Riau Province who experienced fluctuations from 2011- 2020. Allegedly has the effect of several factors. The purpose of this study was to determine the effect of economic growth, fiscal decentralization, and per capita income on poverty in Riau Province. The location of this study was Riau Province which was carried out by analyzing time series data related to each variable in 2011-2019. The analysis used in this study was multiple regression analysis. The results of this study indicate that economic growth has no partially influence on poverty in Riau Province in 2010-2019. Fiscal decentralization has a partially influence on poverty in Riau Province in 2010-2019. Per capita income has a partial influence on poverty in Riau Province in 2010-2019. Economic growth, fiscal decentralization, and per capita income did not have a simultaneous effect on poverty in Riau Province in 2010-2019.Keywords: Poverty, Economy, Fiscal